IDH1 mutations in a Turkey series of primary glioblastoma - Kalkan, R.; Atli, E. I. (WILEY-BLACKWELL, 2014)
FEBS EMBO 2014 Conference, Paris, FRANCE, AUG 30-SEP 04, 2014
Keywords: Glioblastoma Multiforme; IDH1 mutation; Turkey